The Effectiveness of Mindfulness Practices in Alleviating Stress Among Emergency Care Nurses - Nurjanah, Eka; Yuliastuti, Estin; Suyatno, Suyatno (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2025)
Aims: All hospital staff were at risk of experiencing stress, but nurses often faced higher levels of stress, especially in the emergency department. If the stress experienced by nurses was not addressed promptly, it could lead to psychosocial issues and negatively impact their performance. This study evaluated the effectiveness of a 15-minute mindfulness intervention in reducing stress among nurses in the emergency department. Method: This study was a quasi-experimental with a one group pretest-posttest design, conducted from December 15 to 17, 2023, in an emergency department at a hospital in Sragen. A total of 15 respondents were selected using total sampling. This study only utilized 14 items to measure stress of the DASS (Depression Anxiety Stress Scale) before and after the Mindfulness intervention, which was conducted in a group setting for 15 minutes. Data were analyzed using the Wilcoxon Rank Test. Results: The analysis showed a p-value of 0.000 (p<0.05). Conclusion: Mindfulness practices significantly impacted the stress levels of nurses in the emergency department. This study supports the integration of mindfulness practices in stress management programs for emergency department nurses.